Disaggregation of gold nanoparticles by Daphnia magna. Issue 8 (14th September 2018) - Mattsson, Karin; Aguilar, Ruben; Torstensson, Oscar; Perry, Diana; Bernfur, Katja; Linse, Sara; Hansson, Lars-Anders; Åkerfeldt, Karin S.; Cedervall, Tommy
Abstract: The use of manufactured nanomaterials is rapidly increasing, while our understanding of the consequences of releasing these materials into the environment is still limited and many questions remain, for example, how do nanoparticles affect living organisms in the wild? How do organisms adapt and protect themselves from exposure to foreign materials? How does the environment affect the performance of nanoparticles, including their surface properties? In an effort to address these crucial questions, our main aim has been to probe the effects of aquatic organisms on nanoparticle aggregation. We have, therefore, carried out a systematic study with the purpose to disentangle the effects of the freshwater zooplankter, Daphnia magna, on the surface properties, stability, and aggregation properties of gold (Au) nanoparticles under different aqueous conditions as well as identified the proteins bound to the nanoparticle surface. We show that Au nanoparticles aggregate in pure tap water, but to a lesser extent in water that either contains Daphnia or has been pre-conditioned with Daphnia . Moreover, we show that proteins generated by Daphnia bind to the Au nanoparticles and create a modified surface that renders them less prone to aggregation. We conclude that the surrounding milieu, as well as the surface properties of the original Au particles, are important factors in determining how the nanoparticles are affected by biological metabolism. In a broader context, our results show how nanoparticles released into a natural ecosystem become chemically and physically altered through the dynamic interactions between particles and organisms, either through biological metabolism or through the interactions with biomolecules excreted by organisms into the environment.